GABA operates upstream of H⁺-ATPase and improves salinity tolerance in Arabidopsis by enabling cytosolic K⁺ retention and Na⁺ exclusion - Su, Nana; Wu, Qi; Chen, Jiahui; Shabala, Lana; Mithöfer, Axel; Wang, Haiyang; Qu, Mei; Yu, Min; Cui, Jin; Shabala, Sergey (Journal of experimental botany, 2019)
The non-protein amino acid γ-aminobutyric acid (GABA) rapidly accumulates in plant tissues in response to salinity. However, the physiological rationale for this elevation remains elusive. This study compared electrophysiological and whole-plant responses of salt-treated Arabidopsis mutants pop2-5 and gad1,2, which have different abilities to accumulate GABA. The pop2-5 mutant, which was able to overaccumulate GABA in its roots, showed a salt-tolerant phenotype. On the contrary, the gad1,2 mutant, lacking the ability to convert glutamate to GABA, showed oversensitivity to salinity. The greater salinity tolerance of the pop2-5 line was explained by: (i) the role of GABA in stress-induced activation of H⁺-ATPase, thus leading to better membrane potential maintenance and reduced stress-induced K⁺ leak from roots; (ii) reduced rates of net Na⁺ uptake; (iii) higher expression of SOS1 and NHX1 genes in the leaves, which contributed to reducing Na⁺ concentration in the cytoplasm by excluding Na⁺ to apoplast and sequestering Na⁺ in the vacuoles; (iv) a lower rate of H₂O₂ production and reduced reactive oxygen species-inducible K⁺ efflux from root epidermis; and (v) better K⁺ retention in the shoot associated with the lower expression level of GORK channels in plant leaves.